Balikbayang sinta an E. San Juan reader - San Juan, Epifanio 1938- (Ateneo de Manila University Press, 2008)
"Balikbayang Sinta: An E. San Juan Reader" represents an epoch-making anthology of San Juan's recent interventions into cultural studies in this stage of corporate-led globalization. From his pioneering introduction of George Lukac's essays, Marxism and Human Liberation (1972), to his engagement with the debate of racial formations in the last decades of the twentieth century, San Juan has inserted the Philippines into the contemporary discourse on the crisis of the humanities and modern letters. hailed as a scholar of world-historical significance, San Juan sums up forty years of critical reflection on the burning topics of his time in this gathering of essays and interviews that aims to provoke debate on the issue of whether humanity will choose capitalist barbarism or socialism as the future of the planet."--Back cover.